Bispecific killer cell engagers employing species cross-reactive NKG2D binders redirect human and murine lymphocytes to ErbB2/HER2-positive malignancies - Pfeifer Serrahima, Jordi; Schoenfeld, Katrin; Kühnel, Ines; Harwardt, Julia; Macarrón Palacios, Arturo; Prüfer, Maren; Kolaric, Margareta; Oberoi, Pranav; Kolmar, Harald; Wels, Winfried S. (Frontiers in Immunology, 2024)
NKG2D is an activating receptor expressed by natural killer (NK) cells and other cytotoxic lymphocytes that plays a pivotal role in the elimination of neoplastic cells through recognition of different stress-induced cell surface ligands (NKG2DL). To employ this mechanism for cancer immunotherapy, we generated NKG2D-engaging bispecific antibodies that selectively redirect immune effector cells to cancer cells expressing the tumor-associated antigen ErbB2 (HER2). NKG2Dspecific single chain fragment variable (scFv) antibodies cross-reactive toward the human and murine receptors were derived by consecutive immunization of chicken with the human and murine antigens, followed by stringent screening of a yeast surface display immune library. Four distinct species crossreactive (sc) scFv domains were selected, and reformatted into a bispecific engager format by linking them via an IgG4 Fc domain to a second scFv fragment specific for ErbB2. The resulting molecules (termed scNKAB-ErbB2) were expressed as disulfide-linked homodimers, and demonstrated efficient binding to ErbB2-positive cancer cells as well as NKG2D-expressing primary human and murine lymphocytes, and NK-92 cells engineered with chimeric antigen receptors derived from human and murine NKG2D (termed hNKAR and mNKAR). Two of the scNKAB-ErbB2 molecules were found to compete with the natural NKG2D ligand MICA, while the other two engagers interacted with an epitope outside of the ligand binding site. Nevertheless, all four tested scNKAB-ErbB2 antibodies were similarly effective in redirecting the cytotoxic activity of primary human and murine lymphocytes as well as hNKAR-NK-92 and mNKAR-NK-92 cells to ErbB2-expressing targets, suggesting that further development of these species cross-reactive engager molecules for cancer immunotherapy is warranted.